Bias Magnetic Field of Stack Giant Magnetostrictive Actuator: Design, Analysis, and Optimization - Zhaoshu Yang; Zhongbo He; Dongwei Li; Ce Rong (Advances in Materials Science and Engineering)
Many novel applications using giant magnetostrictive actuators (GMA) require their actuators output bidirectional strokes to be large enough to drive the load. In these cases, the sophisticated method to form such a sufficient bias field with minimum power and bulk consumption should be considered in the principal stage of GMA design. This paper concerns the methodology of bias field design for a specific GMA with stack PMs and GMMs (SGMA): both loop and field models for its bias field are established; the optimization method for given SGMA structure is outlined; a prototype is fabricated to verify the theory. Simulation and test results indicate that the bias field could be exerted more easily using SGMA structure; the modeling and optimization methodology for SGMA is valid in practical design.